Adhesive composition for touch panels and adhesive sheet for touch panels

The adhesive composition for touch panels, comprising a specific (meth)acrylic copolymer and antioxidants, addresses the issue of rapid deterioration in high-temperature environments by resisting whitening and maintaining adhesive strength, making it suitable for automotive applications.

JP7600013B2Active Publication Date: 2024-12-16NIPPON CARBIDE KOGYO KK
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021053831
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2024-12-16
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Adhesive compositions for touch panels used in high-temperature environments, such as those found in in-vehicle display devices, face issues with rapid deterioration, leading to decreased adhesive strength and yellowing, which are exacerbated by high temperatures and humidity.

Method used

An adhesive composition for touch panels containing a (meth)acrylic copolymer with 18% or more structural units derived from a monomer with a hydroxyl group, combined with a phenolic antioxidant having a molecular weight of 300 or more and no polymerizable group, and an antioxidant other than phenolic, in specific ratios, to form an adhesive layer that resists whitening and maintains high adhesive strength.

Benefits of technology

The adhesive composition effectively prevents whitening and maintains high adhesive strength even in high-temperature and high-humidity environments, suitable for use in automotive touch panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600013000001
    Figure 0007600013000001
  • Figure 0007600013000002
    Figure 0007600013000002
  • Figure 0007600013000003
    Figure 0007600013000003
Patent Text Reader

Abstract

To provide an adhesive composition for a touch panel, which is hardly whitened even when left standing in a high temperature and high humidity environment, which exhibits high adhesive force to an adherend even when left standing in a high temperature environment, and which can form an adhesive layer hardly turning to yellow, and to provide an adhesive sheet for a touch panel.SOLUTION: An adhesive composition for a touch panel which includes: a (meth)acrylic copolymer (A) containing a constitutional unit derived from a monomer having a hydroxy group of 18 mass% or more based on total constitutional units; a phenolic antioxidant (B) having molecular weight of 300 or more and having no polymerizable group; and an antioxidant (C) other than the phenolic antioxidant, in which a content of the phenolic antioxidant (B) is 0.1-3.0 pts.mass based on the (meth)acrylic copolymer (A) of 100 pts.mass, and a content of the antioxidant (C) other than the phenolic antioxidant is 0.05-0.50 pts.mass based on the (meth)acrylic copolymer (A) of 100 pts.mass, and an adhesive sheet for a touch panel are disclosed.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a pressure-sensitive adhesive composition for a touch panel and a pressure-sensitive adhesive sheet for a touch panel. [Background technology]

[0002] In portable electronic devices such as mobile phones and mobile terminals, touch panels are often used as input devices. A cover panel is provided on the surface of the touch panel in order to protect the touch panel. In order to ensure visibility, the touch panel and the cover panel are generally bonded together via an adhesive layer formed of an acrylic adhesive composition.

[0003] A pressure-sensitive adhesive composition used in a touch panel (so-called pressure-sensitive adhesive composition for a touch panel) is required to have various properties. For example, a portable electronic device is carried and used in various places, and may be left in a high temperature environment or a high temperature and high humidity environment. When a portable electronic device equipped with a touch panel is placed in a high temperature environment for a long period of time, the pressure-sensitive adhesive layer attached to the touch panel may turn yellow or the adhesive strength of the pressure-sensitive adhesive layer may decrease. In addition, when a portable electronic device equipped with a touch panel is placed in a high temperature and high humidity environment for a long period of time, the pressure-sensitive adhesive layer attached to the touch panel may turn white. Such yellowing and whitening of the pressure-sensitive adhesive layer and the decrease in adhesive strength of the pressure-sensitive adhesive layer are factors that impair the commercial value of the portable electronic device. For this reason, a pressure-sensitive adhesive composition for a touch panel is required to be able to form a pressure-sensitive adhesive layer whose performance and appearance are unlikely to change even when placed in a high temperature environment or a high temperature and high humidity environment.

[0004] As an example of an adhesive composition that satisfies such requirements, Patent Document 1 reports an adhesive composition that contains an acrylic polymer having a weight average molecular weight of 200,000 to 2,000,000 and an acid value of 5.0 or less, which is obtained by copolymerizing 0.1 to 10 parts by weight of a copolymerizable monomer having a hydroxyl group with 100 parts by weight of a total of (meth)acrylic acid alkyl ester monomers having 1 to 18 carbon atoms in the alkyl group; a specific amount of a diester compound having a specific structure; an isocyanate-based crosslinking agent; and at least one antioxidant selected from a phenol-based antioxidant and a phosphite-based antioxidant. The adhesive composition described in Patent Document 1 is said to be capable of forming an adhesive layer that does not peel off from an adherend even when left in a high-temperature environment at an atmospheric temperature of 80°C for 250 hours, and does not become cloudy even when left in a high-temperature, high-humidity environment at an atmospheric temperature of 85°C and 85% RH for 240 hours. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-64282 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, touch panels are often used as input devices in on-vehicle display devices such as car navigation systems and instrument panels. From the viewpoint of reliability, the adhesive composition used in the touch panel mounted on the on-vehicle display device is required to be able to form an adhesive layer that is not easily deteriorated even when placed in an environment with a higher temperature (for example, 130°C) than previously assumed. However, in a high-temperature environment such as 130°C, the thermal deterioration of the adhesive layer is accelerated, so that the adhesive strength of the adhesive layer is likely to decrease rapidly and the adhesive layer is likely to turn yellow. Some of the touch panels in recent years have shapes such as curved shapes and irregular shapes from the viewpoint of design and operability. The adhesive layer attached to such a shape requires a higher adhesive strength than before, and it is therefore desirable that the adhesive layer can maintain a high adhesive strength even when placed in a high-temperature environment. As described above, the adhesive composition for a touch panel is required to be able to form an adhesive layer that is resistant to whitening even when placed in a high-temperature and high-humidity environment, and in addition, to be able to form an adhesive layer that is resistant to loss of adhesive strength and yellowing even when placed in a high-temperature environment such as 130°C.

[0007] An object of one embodiment of the present disclosure is to provide a pressure-sensitive adhesive composition for touch panels that is resistant to whitening even when placed in a high-temperature, high-humidity environment, and that is capable of forming a pressure-sensitive adhesive layer that exhibits high adhesive strength to an adherend and is resistant to yellowing even when placed in a high-temperature environment. The problem that another embodiment of the present disclosure aims to solve is to provide an adhesive sheet for touch panels that is resistant to whitening even when placed in a high-temperature, high-humidity environment, and has an adhesive layer that exhibits high adhesive strength to an adherend and is resistant to yellowing even when placed in a high-temperature environment. [Means for solving the problem]

[0008] Specific means for solving the problems include the following aspects. <1> a (meth)acrylic copolymer (A) containing 18% by mass or more of structural units derived from a monomer having a hydroxyl group relative to the total structural units; (B) a phenol-based antioxidant having a molecular weight of 300 or more and having no polymerizable group; and an antioxidant (C) other than a phenol-based antioxidant, the content of the phenol-based antioxidant (B) is 0.1 parts by mass to 3.0 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A); A pressure-sensitive adhesive composition for touch panels, wherein the content of the antioxidant (C) other than the phenol-based antioxidant is 0.05 to 0.50 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A). <2> The phenol-based antioxidant (B) is a compound having 1 to 3 aromatic rings in one molecule. <1> The pressure-sensitive adhesive composition for a touch panel according to claim 1 . <3> The antioxidant (C) other than the phenol-based antioxidant is at least one antioxidant selected from the group consisting of phosphorus-based antioxidants and sulfur-based antioxidants. <1> or <2> The pressure-sensitive adhesive composition for a touch panel according to claim 1 . <4> The ratio of the mass of the phenol-based antioxidant (B) to the mass of the antioxidant (C) other than the phenol-based antioxidant is 1.3 to 15.0. <1> ~ <3> 13. The pressure-sensitive adhesive composition for a touch panel according to claim 12. <5> The weight average molecular weight of the (meth)acrylic copolymer (A) is 200,000 to 900,000. <1> ~ <4> 13. The pressure-sensitive adhesive composition for a touch panel according to claim 12. <6> The (meth)acrylic copolymer (A) has a glass transition temperature of -40°C to -5°C. <1> ~ <5> 13. The pressure-sensitive adhesive composition for a touch panel according to claim 12. <7> Contains isocyanate crosslinking agent <1> ~ <6> 13. The pressure-sensitive adhesive composition for a touch panel according to claim 12. <8> Used in automotive touch panels <1> ~ <7> 13. The pressure-sensitive adhesive composition for a touch panel according to claim 12. <9> <1> ~ <7> 13. An adhesive sheet for a touch panel, comprising an adhesive layer formed from the adhesive composition for a touch panel according to any one of claims 1 to 22. <10> Used in automotive touch panels <9> The adhesive sheet for a touch panel according to claim 1. Effect of the Invention

[0009] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition for touch panels which is capable of forming a pressure-sensitive adhesive layer which is resistant to whitening even when placed in a high-temperature and high-humidity environment, exhibits high adhesive strength to an adherend even when placed in a high-temperature environment, and is resistant to yellowing. According to another embodiment of the present disclosure, there is provided an adhesive sheet for touch panels, which includes an adhesive layer that is resistant to whitening even when placed in a high temperature and high humidity environment, exhibits high adhesive strength to an adherend even when placed in a high temperature environment, and is resistant to yellowing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The adhesive composition for touch panels and the adhesive sheet for touch panels of the present disclosure will be described in detail below. The following description of the requirements may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.

[0011] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values ​​before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.

[0012] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when a plurality of substances corresponding to each component are present in the adhesive composition for a touch panel, the amount of each component in the adhesive composition for a touch panel means the total amount of the plurality of substances present in the adhesive composition for a touch panel, unless otherwise specified.

[0013] In the present disclosure, "(meth)acrylic copolymer" means a copolymer in which the content of structural units derived from monomers having a (meth)acryloyl group is 50 mass% or more of all structural units (i.e., all structural units of the (meth)acrylic copolymer).

[0014] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".

[0015] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.

[0016] [Adhesive composition for touch panels] The pressure-sensitive adhesive composition for touch panels (hereinafter, also simply referred to as "pressure-sensitive adhesive composition") of the present disclosure comprises a (meth)acrylic copolymer (A) containing 18% by mass or more of structural units derived from a monomer having a hydroxyl group, based on all structural units; a phenolic antioxidant (B) having a molecular weight of 300 or more and having no polymerizable group; and an antioxidant (C) other than the phenolic antioxidant, wherein the content of the phenolic antioxidant (B) is 0.1 to 3.0 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A), and the content of the antioxidant (C) other than the phenolic antioxidant is 0.05 to 0.50 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A). Hereinafter, "the (meth)acrylic copolymer (A) containing 18 mass% or more of structural units derived from a monomer having a hydroxyl group, based on the total structural units" will be simply referred to as "the (meth)acrylic copolymer (A)", "the phenolic antioxidant (B) having a molecular weight of 300 or more and having no polymerizable group" will be simply referred to as "the phenolic antioxidant (B)", and "the antioxidant (C) other than a phenolic antioxidant" will be simply referred to as "the antioxidant (C)".

[0017] The pressure-sensitive adhesive composition of the present disclosure, by having the above-described configuration, is capable of forming a pressure-sensitive adhesive layer that is resistant to whitening even when placed in a high-temperature, high-humidity environment, and that exhibits high adhesive strength to an adherend and is resistant to yellowing even when placed in a high-temperature environment. The reason why the pressure-sensitive adhesive composition of the present disclosure can exhibit such an effect is unclear, but the present inventors speculate as follows, however, the following speculation is not intended to limit the pressure-sensitive adhesive composition of the present disclosure, but is merely an example.

[0018] When a mobile electronic device equipped with a touch panel is placed in a high-temperature and high-humidity environment for a long period of time, the adhesive layer attached to the touch panel may whiten. When the adhesive layer whitens, visibility decreases, and the commercial value of the mobile electronic device is lost. The present inventors have conducted extensive research to realize a pressure-sensitive adhesive composition capable of forming a pressure-sensitive adhesive layer that is resistant to whitening even when placed in a high-temperature, high-humidity environment, and have found that increasing the number of hydroxyl groups in the (meth)acrylic copolymer contained in the pressure-sensitive adhesive composition can suppress the whitening of the pressure-sensitive adhesive layer when placed in a high-temperature, high-humidity environment. However, on the other hand, it has been found that increasing the number of hydroxyl groups in the (meth)acrylic copolymer reduces the durability of the pressure-sensitive adhesive layer at high temperatures, causes the pressure-sensitive adhesive layer to yellow, and reduces the adhesive strength of the pressure-sensitive adhesive layer. When an adhesive layer containing many hydroxyl groups in the (meth)acrylic copolymer is placed in a high temperature environment for a long period of time, it is believed that a large amount of peroxy radicals resulting from the hydroxyl groups in the (meth)acrylic copolymer are generated in the adhesive layer. It is presumed that the generated peroxy radicals oxidize and deteriorate the (meth)acrylic polymer, causing a rapid decrease in the adhesive strength of the adhesive layer and a rapid yellowing of the adhesive layer.

[0019] In contrast, the pressure-sensitive adhesive composition of the present disclosure contains a specific amount of a phenolic antioxidant (B) having a specific molecular weight and structure in addition to the (meth)acrylic copolymer (A) containing many hydroxyl groups, and therefore in the pressure-sensitive adhesive layer formed, the generated peroxy radicals are captured and inactivated by the phenolic antioxidant (B). The peroxy radicals are converted to hydroperoxides by the phenolic antioxidant (B), but the hydroperoxides are unstable and generate peroxy radicals by thermal decomposition. The generated peroxy radicals are captured and inactivated again by the phenolic antioxidant (B), but when the phenolic antioxidant (B) is oxidized, a quinone compound, which is one of the factors that cause the pressure-sensitive adhesive layer to yellow, is generated. In contrast, the pressure-sensitive adhesive composition of the present disclosure contains, in addition to the phenolic antioxidant (B), a specific amount of an antioxidant (C) other than a phenolic antioxidant. In the pressure-sensitive adhesive layer formed, the antioxidant (C) decomposes unstable hydroperoxides into more stable alcohols, thereby stopping the chain reaction described above. From the above, it is presumed that the pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that is resistant to whitening even when placed in a high-temperature, high-humidity environment, and that exhibits high adhesive strength to an adherend and is resistant to yellowing even when placed in a high-temperature environment.

[0020] [(Meth)acrylic copolymer (A)] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic copolymer (A) containing 18 mass % or more of structural units derived from a monomer having a hydroxyl group, based on all structural units. The pressure-sensitive adhesive composition of the present disclosure may contain only one type of (meth)acrylic copolymer (A), or may contain two or more types.

[0021] <Structural Unit Derived from Monomer Having a Hydroxyl Group> The (meth)acrylic copolymer (A) contains 18 mass % or more of structural units derived from monomers having a hydroxyl group, based on the total amount of structural units. In the present disclosure, a "structural unit derived from a monomer having a hydroxyl group" refers to a structural unit formed by addition polymerization of a monomer having a hydroxyl group.

[0022] The type of the monomer having a hydroxyl group is not particularly limited. An example of a monomer having a hydroxyl group is a monomer having at least one hydroxyl group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a styryl group, a maleimide group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.

[0023] Specific examples of monomers having a hydroxyl group include hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, and 1,1-dimethyl-3-hydroxybutyl. (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. Among these, as the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl (meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with crosslinking agents (particularly isocyanate-based crosslinking agents), hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and at least one selected from 2-hydroxyethyl acrylate (2HEA) and 4-hydroxybutyl acrylate (4HBA) is particularly preferred.

[0024] The (meth)acrylic copolymer (A) may contain only one type of structural unit derived from a monomer having a hydroxyl group, or may contain two or more types.

[0025] The content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer (A) is 18 mass % or more based on all structural units of the (meth)acrylic copolymer (A). When the content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer (A) is 18 mass% or more relative to all structural units of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive layer formed tends to be less susceptible to whitening even when placed in a high-temperature, high-humidity environment. From this viewpoint, the content of structural units derived from monomers having a hydroxyl group in the (meth)acrylic copolymer (A) is 18% by mass or more, preferably 23% by mass or more, more preferably 28% by mass or more, and even more preferably 33% by mass or more, based on the total structural units of the (meth)acrylic copolymer (A). The upper limit of the content of the structural units derived from the monomer having a hydroxyl group in the (meth)acrylic copolymer (A) is not particularly limited, but from the viewpoint of the production suitability of the (meth)acrylic copolymer (A), for example, it is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on the total structural units of the (meth)acrylic copolymer (A).

[0026] <Structural Unit Derived from (Meth)acrylic Acid Alkyl Ester Monomer> The (meth)acrylic copolymer (A) preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. The structural units derived from the (meth)acrylic acid alkyl ester monomer can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.

[0027] In the present disclosure, the term "structural unit derived from a (meth)acrylic acid alkyl ester monomer" refers to a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer.

[0028] The type of the (meth)acrylic acid alkyl ester monomer is not particularly limited. In addition, the "(meth)acrylic acid alkyl ester monomer" in the (meth)acrylic copolymer (A) does not include a monomer corresponding to the monomer having a hydroxyl group described above and a monomer corresponding to a monomer having a carboxy group described below. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.

[0029] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Among these, the (meth)acrylic acid alkyl ester monomer is preferably at least one selected from, for example, methyl acrylate (MA), ethyl acrylate (EA), n-butyl acrylate (n-BA), and 2-ethylhexyl acrylate (2EHA).

[0030] When the (meth)acrylic copolymer (A) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, it may contain only one type of structural unit derived from the (meth)acrylic acid alkyl ester monomer, or it may contain two or more types of structural units derived from the (meth)acrylic acid alkyl ester monomer.

[0031] When the (meth)acrylic copolymer (A) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer in the (meth)acrylic copolymer (A) is not particularly limited, but is, for example, preferably 50 mass% or more, more preferably 50 mass% to 82 mass%, even more preferably 50 mass% to 77 mass%, even more preferably 50 mass% to 72 mass%, and particularly preferably 50 mass% to 67 mass%, relative to all structural units of the (meth)acrylic copolymer (A). Here, the content of structural units derived from (meth)acrylic acid alkyl ester monomers in the (meth)acrylic copolymer (A) being 50 mass% or more relative to the total structural units of the (meth)acrylic copolymer (A) means that the structural units derived from (meth)acrylic acid alkyl ester monomers are contained as the main component of the structural units constituting the (meth)acrylic copolymer (A).

[0032] <Structural Unit Derived from Monomer Having a Carboxy Group> The (meth)acrylic copolymer (A) may contain a structural unit derived from a monomer having a carboxy group. When the (meth)acrylic copolymer (A) contains a structural unit derived from a monomer having a carboxy group, the carboxy group acts as an acid catalyst in the urethane reaction between the hydroxyl group in the (meth)acrylic copolymer (A) and the isocyanate group in the isocyanate crosslinking agent, and therefore the curing time can be shortened, and the productivity of the pressure-sensitive adhesive sheet, for example, can be improved. In the present disclosure, a "structural unit derived from a monomer having a carboxy group" refers to a structural unit formed by addition polymerization of a monomer having a carboxy group.

[0033] The type of the monomer having a carboxy group is not particularly limited. An example of a monomer having a carboxy group is a monomer having at least one carboxy group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a styryl group, a maleimide group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.

[0034] Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,Ma Examples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate.

[0035] When the (meth)acrylic copolymer (A) contains a structural unit derived from a monomer having a carboxy group, it may contain only one type of structural unit derived from a monomer having a carboxy group, or it may contain two or more types of structural units derived from a monomer having a carboxy group.

[0036] The content of structural units derived from monomers having a carboxy group in the (meth)acrylic copolymer (A) is not particularly limited, but from the viewpoint of improving the productivity of the pressure-sensitive adhesive sheet by shortening the curing time, for example, it is preferable that the content be 0.1 mass% or more based on the total structural units of the (meth)acrylic copolymer (A). For example, when the adherend includes a metal member, from the viewpoint of suppressing corrosion of the metal, it is preferable that the (meth)acrylic copolymer (A) does not contain a structural unit derived from a monomer having a carboxy group, or the content of the structural unit derived from a monomer having a carboxy group is more than 0% by mass and 2.0% by mass or less with respect to the total structural units of the (meth)acrylic copolymer (A), it is more preferable that the (meth)acrylic copolymer (A) does not contain a structural unit derived from a monomer having a carboxy group, or the content of the structural unit derived from a monomer having a carboxy group is more than 0% by mass and 1.0% by mass or less with respect to the total structural units of the (meth)acrylic copolymer (A), it is even more preferable that the (meth)acrylic copolymer (A) does not contain a structural unit derived from a monomer having a carboxy group, or the content of the structural unit derived from a monomer having a carboxy group is more than 0% by mass and 0.5% by mass or less with respect to the total structural units of the (meth)acrylic copolymer (A), and it is particularly preferable that the (meth)acrylic copolymer (A) does not contain a structural unit derived from a monomer having a carboxy group.

[0037] <Other building blocks> The (meth)acrylic copolymer (A) may contain structural units (so-called other structural units) other than the structural units described above, if necessary, within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.

[0038] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.

[0039] When the (meth)acrylic copolymer (A) contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.

[0040] When the (meth)acrylic copolymer (A) contains other structural units, the content of the other structural units in the (meth)acrylic copolymer (A) is not particularly limited and can be appropriately set depending on the purpose as long as the effects of the pressure-sensitive adhesive composition of the present disclosure are not impaired.

[0041] <<Weight average molecular weight of (meth)acrylic copolymer (A)>> The weight average molecular weight (also referred to as "Mw") of the (meth)acrylic copolymer (A) is not particularly limited, but is, for example, preferably 100,000 to 1,000,000, more preferably 200,000 to 900,000, even more preferably 300,000 to 800,000, and particularly preferably 400,000 to 700,000. When the (meth)acrylic copolymer (A) has a weight average molecular weight of 100,000 or more, the adhesive strength of the pressure-sensitive adhesive layer to an adherend placed in a high-temperature environment tends to be higher. When the weight average molecular weight of the (meth)acrylic copolymer (A) is 1,000,000 or less, the initial adhesive strength of the pressure-sensitive adhesive layer to an adherend tends to be higher.

[0042] The weight average molecular weight of the (meth)acrylic copolymer (A) is a value determined by the following method, specifically, according to the following (1) to (3). (1) A solution of the (meth)acrylic copolymer (A) is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the (meth)acrylic copolymer (A). (2) Using the film-like (meth)acrylic copolymer (A) obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the (meth)acrylic copolymer (A) in the sample solution. (3) The weight average molecular weight of the (meth)acrylic copolymer (A) is determined, in terms of standard polystyrene, by gel permeation chromatography (GPC) under the following conditions.

[0043] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min

[0044] The weight average molecular weight of the (meth)acrylic copolymer (A) can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, etc. when polymerizing the monomers.

[0045] <<Glass transition temperature of (meth)acrylic copolymer (A)>> The glass transition temperature (hereinafter also referred to as "Tg") of the (meth)acrylic copolymer (A) is not particularly limited, but is, for example, preferably from -50°C to -5°C, more preferably from -40°C to -5°C, and even more preferably from -40°C to -10°C. When the (meth)acrylic copolymer (A) has a glass transition temperature of -50°C or higher, the adhesive strength of the pressure-sensitive adhesive layer to an adherend placed in a high-temperature environment tends to be higher. When the (meth)acrylic copolymer (A) has a glass transition temperature of −5° C. or lower, the pressure-sensitive adhesive layer tends to have a higher initial adhesive strength to an adherend.

[0046] The glass transition temperature of the (meth)acrylic copolymer (A) is a value calculated from the following formula 1, and converted from the absolute temperature (unit: K); the same applies below) into Celsius temperature (unit: °C); the same applies below). 1 / Tg=m1 / Tg1+m2 / Tg2+ +m(k-1) / Tg(k-1)+mk / Tgk (Formula 1)

[0047] In formula 1, Tg1, Tg2, , Tg(k-1), and Tgk respectively represent the glass transition temperatures expressed as absolute temperatures when each monomer constituting the (meth)acrylic copolymer (A) is made into a homopolymer. m1, m2, , m(k-1), and mk respectively represent the molar fractions of each monomer constituting the (meth)acrylic copolymer (A), and m1+m2+···+m(k-1)+mk=1. Note that absolute temperatures can be converted to Celsius temperatures by subtracting 273 from the absolute temperature, and Celsius temperatures can be converted to absolute temperatures by adding 273 to the Celsius temperature.

[0048] In the present disclosure, the "glass transition temperature expressed as absolute temperature when made into a homopolymer" refers to the glass transition temperature expressed as absolute temperature of a homopolymer produced by polymerizing the monomer alone. The glass transition temperature of the homopolymer was measured using a differential scanning calorimeter (DSC) [model: EXSTAR6000, manufactured by Seiko Instruments Inc.] under conditions of a nitrogen gas flow, a measurement sample of 10 mg, and a heating rate of 10°C / min, and the inflection point of the obtained DSC curve was taken as the glass transition temperature of the homopolymer.

[0049] The glass transition temperatures of representative monomers, expressed in Celsius degrees when made into homopolymers, are: 2-ethylhexyl acrylate (2EHA) -76°C, 2-ethylhexyl methacrylate (2EHMA) -10°C, n-butyl acrylate (n-BA) -57°C, n-butyl methacrylate (n-BMA) 21°C, t-butyl acrylate (t-BA) 41°C, t-butyl methacrylate (t-BMA) 107°C, i-butyl methacrylate (i-BMA) 48°C, methyl acrylate (MA) 5°C, methyl methacrylate (MMA) 103°C, isobornyl methacrylate (IBXMA) 155°C, isobornyl acrylate (IBXA) 96°C, and ethyl acrylate ( EA) at -27°C, methacrylic acid (MAA) at 185°C, 4-hydroxybutyl acrylate (4HBA) at -39°C, 2-hydroxyethyl acrylate (2HEA) at -15°C, 2-hydroxyethyl methacrylate (2HEMA) at 55°C, 2-hydroxypropyl acrylate (2HPA) at -7°C, acrylic acid (AA) at 163°C, n-octyl acrylate (n-OA) at -65°C, i-octyl acrylate (i-OA) at -75°C, i-decyl acrylate at -62°C, dimethylaminoethyl methacrylate (DM) at 18°C, ω-carboxy-polycaprolactone (n≒2) monoacrylate at -30°C, and 2-acryloyloxyethyl-succinic acid at -40°C.

[0050] The glass transition temperature of the (meth)acrylic copolymer (A) can be appropriately adjusted, for example, by using two or more monomers having different glass transition temperatures when formed into homopolymers.

[0051] <<Content of (meth)acrylic copolymer (A)>> The content of the (meth)acrylic copolymer (A) in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 50.0 mass% to 99.85 mass%, more preferably 60.0 mass% to 99.8 mass%, and even more preferably 70.0 mass% to 99.5 mass%, relative to the total solid content in the pressure-sensitive adhesive composition. In the present disclosure, the "total solid content in the PSA composition" means the total mass of the PSA composition when the PSA composition does not contain a solvent, and means the mass of the residue remaining after removing the solvent from the PSA composition when the PSA composition contains a solvent. In this disclosure, "solvent" means water and organic solvents.

[0052] [Method for producing (meth)acrylic copolymer (A)] The method for producing the (meth)acrylic copolymer (A) is not particularly limited. The (meth)acrylic copolymer (A) can be produced by polymerizing the above-mentioned monomers by a known polymerization method typified by, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As a polymerization method, a solution polymerization method is preferred in that the processing steps are relatively simple and can be carried out in a short time when preparing the pressure-sensitive adhesive composition of the present disclosure after production.

[0053] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and reacted for several hours, for example, at the reflux temperature of the organic solvent while stirring. In this case, at least a part of the organic solvent, the monomer, the polymerization initiator, and the chain transfer agent used as required may be added successively. The reaction may also be carried out in a nitrogen gas flow.

[0054] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. Specific examples of aromatic hydrocarbon compounds include benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha. Specific examples of aliphatic or alicyclic hydrocarbon compounds include n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirits, petroleum naphtha, and turpentine oil. Specific examples of the ester compound include ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate. Specific examples of ketone compounds include acetone, methyl ethyl ketone, methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone. Specific examples of glycol ether compounds include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether. Specific examples of the alcohol compound include methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.

[0055] In producing the (meth)acrylic copolymer (A), it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction of an aromatic hydrocarbon compound, an ester compound, a ketone compound, etc., and in particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the (meth)acrylic copolymer (A) and the ease of the polymerization reaction.

[0056] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.

[0057] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Specific examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the (meth)acrylic copolymer (A), it is preferable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and it is particularly preferable to use an azo compound.

[0058] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.

[0059] The amount of the polymerization initiator used is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the desired (meth)acrylic copolymer (A).

[0060] In producing the (meth)acrylic copolymer (A), a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, α-methylstyrene, anthracene, phenanthrene, fluorene, 9-phenylfluorene, p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, p-nitrotoluene, benzoquinone, 2,3,5,6-tetramethyl-p-benzoquinone, tributylborane, tetramethyl ... Examples of such mercaptan compounds include carbon bromide, carbon tetrachloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, 3-chloro-1-propene, chloral, furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, thiophenol, toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, pinene, and terpinolene.

[0061] When a chain transfer agent is used in producing the (meth)acrylic copolymer (A), the amount of the chain transfer agent used is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target (meth)acrylic copolymer (A).

[0062] The polymerization temperature is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the desired (meth)acrylic copolymer (A).

[0063] [Phenol-based antioxidant (B)] The pressure-sensitive adhesive composition of the present disclosure contains a phenolic antioxidant (B) having a molecular weight of 300 or more and having no polymerizable group. The content of the phenolic antioxidant (B) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 3.0 parts by mass relative to 100 parts by mass of the above-mentioned (meth)acrylic copolymer (A).

[0064] The type of the phenol-based antioxidant (B) is not particularly limited as long as it has a molecular weight of 300 or more and does not have a polymerizable group. The molecular weight of the phenolic antioxidant (B) is 300 or more, preferably 350 or more, and more preferably 400 or more. When the phenolic antioxidant (B) is a phenolic antioxidant having a molecular weight of 300 or more, the pressure-sensitive adhesive layer formed tends to exhibit high adhesive strength to the adherend even when placed in a high-temperature environment. The upper limit of the molecular weight of the phenol-based antioxidant (B) is not particularly limited, but is preferably, for example, 1,500 or less.

[0065] The phenol-based antioxidant (B) is a phenol-based antioxidant having no polymerizable group. When the phenol-based antioxidant (B) is a phenol-based antioxidant having no polymerizable group, the pressure-sensitive adhesive layer formed tends to exhibit high adhesion to the adherend even when placed in a high-temperature environment. Also, when the phenol-based antioxidant (B) is a phenol-based antioxidant having no polymerizable group, the pressure-sensitive adhesive layer formed tends to be less prone to yellowing even when placed in a high-temperature environment.

[0066] The type of the polymerizable group is not particularly limited as long as it is a group that is involved in a polymerization reaction. Examples of the polymerizable group include an ethylenically unsaturated group and a cationic polymerizable group.Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a styryl group, a maleimide group, a (meth)acrylamide group, and a (meth)acryloyl group.Specific examples of the cationic polymerizable group include an epoxy group and an oxetane group.

[0067] The phenol-based antioxidant (B) is preferably a compound having 1 to 4 aromatic rings in one molecule, more preferably a compound having 1 to 3 aromatic rings, and even more preferably a compound having 1 or 2 aromatic rings. When the phenol-based antioxidant (B) is a compound having 1 to 4 aromatic rings in one molecule, the pressure-sensitive adhesive layer placed in a high-temperature environment tends to be less susceptible to yellowing.

[0068] The aromatic ring includes, for example, an aromatic hydrocarbon ring. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring. The aromatic ring is preferably a benzene ring.

[0069] The phenol-based antioxidant (B) is preferably a compound having a substituent at the site adjacent to the phenolic hydroxyl group (ortho position). The substituent is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 8 carbon atoms, and further preferably an alkyl group having 1 to 4 carbon atoms.

[0070] As the phenol-based antioxidant (B), commercially available products can be used. Examples of commercially available phenolic antioxidants (B) include "ADK STAB (registered trademark) AO-20", "ADK STAB (registered trademark) AO-30", "ADK STAB (registered trademark) AO-40", "ADK STAB (registered trademark) AO-50", "ADK STAB (registered trademark) AO-60", "ADK STAB (registered trademark) AO-80", and "ADK STAB (registered trademark) AO-330" (all manufactured by ADEKA CORPORATION), "Irganox (registered trademark) 1010", "Irganox (registered trademark) 1035", "Irganox (registered trademark) 1076", "Irganox (registered trademark) 1135", "Irganox (registered trademark) 1330", "Irganox (registered trademark) 245", "Irganox (registered trademark) 565", and "Irganox (registered trademark) 3114" (all manufactured by BASF Japan Ltd.), and "Sumilizer (registered trademark) "GA-80" (manufactured by Sumitomo Chemical Co., Ltd.) and "Tocopherol" (manufactured by Mitsubishi Chemical Foods Co., Ltd.).

[0071] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of phenolic antioxidant (B), or may contain two or more types.

[0072] The content of the phenol-based antioxidant (B) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 3.0 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A). When the content of the phenolic antioxidant (B) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive layer formed tends to exhibit high adhesive strength to the adherend even when placed in a high-temperature environment. From this viewpoint, the content of the phenolic antioxidant (B) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer (A), preferably 0.3 parts by mass or more, and more preferably 0.5 parts by mass or more. When the content of the phenolic antioxidant (B) in the pressure-sensitive adhesive composition of the present disclosure is 3.0 parts by mass or less per 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive layer formed tends to be less prone to yellowing even when placed in a high-temperature environment. From such a viewpoint, the content of the phenolic antioxidant (B) in the pressure-sensitive adhesive composition of the present disclosure is 3.0 parts by mass or less, preferably 2.0 parts by mass or less, more preferably 1.0 part by mass or less, and even more preferably 0.8 parts by mass or less, per 100 parts by mass of the (meth)acrylic copolymer (A).

[0073] In the pressure-sensitive adhesive composition of the present disclosure, the ratio of the mass content of the phenol-based antioxidant (B) to the mass content of an antioxidant (C) other than a phenol-based antioxidant described below [mass content of phenol-based antioxidant (B) / mass content of antioxidant (C)] is not particularly limited, but is, for example, preferably 1.0 to 30.0, more preferably 1.3 to 15.0, even more preferably 1.5 to 10.0, and particularly preferably 3.0 to 8.0. In the pressure-sensitive adhesive composition of the present disclosure, when the ratio of the mass content of the phenol-based antioxidant (B) to the mass content of an antioxidant (C) other than a phenol-based antioxidant described below [mass content of phenol-based antioxidant (B) / mass content of antioxidant (C)] is 1.0 or more, the pressure-sensitive adhesive layer tends to have higher adhesive strength to an adherend placed in a high-temperature environment. In the pressure-sensitive adhesive composition of the present disclosure, when the ratio of the mass content of the phenol-based antioxidant (B) to the mass content of an antioxidant (C) other than a phenol-based antioxidant described below [mass content of phenol-based antioxidant (B) / mass content of antioxidant (C)] is 30.0 or less, the pressure-sensitive adhesive layer placed in a high-temperature environment tends to be less susceptible to yellowing.

[0074] [Antioxidants (C)] The pressure-sensitive adhesive composition of the present disclosure contains an antioxidant (C) other than a phenol-based antioxidant. The content of the antioxidant (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.05 to 0.50 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A) described above.

[0075] The molecular weight of the antioxidant (C) is not particularly limited, but is preferably 300 to 1,500, for example. The antioxidant (C) preferably does not have a polymerizable group. Specific examples of the polymerizable group in the antioxidant (C) are similar to those in the phenol-based antioxidant (B), and therefore, description thereof will be omitted here.

[0076] The type of antioxidant (C) is not particularly limited as long as it is an antioxidant other than a phenol-based antioxidant. For example, it is preferable that the antioxidant (C) is at least one antioxidant selected from the group consisting of phosphorus-based antioxidants and sulfur-based antioxidants. Examples of phosphorus-based antioxidants include phosphite compounds. Examples of sulfur-based antioxidants include thioether compounds.

[0077] As the antioxidant (C), a commercially available product can be used. Examples of commercially available antioxidants (C) include phosphorus-based antioxidants "ADK STAB (registered trademark) PEP-8", "ADK STAB (registered trademark) PEP-36", "ADK STAB (registered trademark) HP-10", "ADK STAB (registered trademark) 2112", "ADK STAB (registered trademark) 1178", "ADK STAB (registered trademark) 1500", "ADK STAB (registered trademark) C", "ADK STAB (registered trademark) 135A", "ADK STAB (registered trademark) 3010", and "ADK STAB (registered trademark) TPP" (all manufactured by ADEKA Corporation), as well as "Irgafos (registered trademark) 168" (manufactured by BASF Japan Ltd.). In addition, examples of commercially available antioxidants (C) include sulfur-based antioxidants "ADK STAB (registered trademark) AO-26," "ADK STAB (registered trademark) AO-412S," and "ADK STAB (registered trademark) AO-503" (all manufactured by ADEKA CORPORATION), "Irganox (registered trademark) PS800FL" and "Irganox (registered trademark) PS802FL" (all manufactured by BASF Japan Ltd.), and "Sumilizer (registered trademark) TP-D" (manufactured by Sumitomo Chemical Co., Ltd.).

[0078] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of antioxidant (C), or may contain two or more types.

[0079] The content of the antioxidant (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.05 to 0.50 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A). When the content of the antioxidant (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive layer formed tends to be less prone to yellowing even when placed in a high-temperature environment. From such a viewpoint, the content of the antioxidant (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more, preferably 0.08 parts by mass or more, and more preferably 0.10 parts by mass or more, per 100 parts by mass of the (meth)acrylic copolymer (A). When the content of the antioxidant (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.50 parts by mass or less per 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive layer formed tends to exhibit high initial adhesive strength to an adherend and to retain high adhesive strength even when placed in a high-temperature environment. From such a viewpoint, the content of the antioxidant (C) in the pressure-sensitive adhesive composition of the present disclosure is 0.50 parts by mass or less, preferably 0.30 parts by mass or less, more preferably 0.20 parts by mass or less, and even more preferably 0.15 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer (A).

[0080] [Crosslinking Agent] The pressure-sensitive adhesive composition of the present disclosure preferably contains a crosslinking agent. When the pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent, the gel fraction of the pressure-sensitive adhesive layer formed is increased, and the phenomenon of the pressure-sensitive adhesive layer adhering to a cutting blade (so-called glue residue) is less likely to occur even when an article having the pressure-sensitive adhesive layer is processed into a complex shape, which is preferable from the standpoint of processability.

[0081] The type of crosslinking agent is not particularly limited. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and a metal chelate-based crosslinking agent.

[0082] In this disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound). The term "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (so-called bifunctional or higher epoxy compound). The term "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent.

[0083] As the crosslinking agent, an isocyanate-based crosslinking agent is preferred. The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.

[0084] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).

[0085] When the pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent, it may contain only one type of crosslinking agent, or may contain two or more types of crosslinking agents.

[0086] When the pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent, the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but is, for example, preferably 0.1 to 3.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, even more preferably 0.1 to 1.0 part by mass, and particularly preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer (A). When the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is within the above range relative to 100 parts by mass of the (meth)acrylic copolymer (A), the pressure-sensitive adhesive layer tends to have higher adhesive strength to an adherend placed in a high-temperature environment.

[0087] [Organic Solvent] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent. When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the coatability can be further improved. As the organic solvent, for example, the same organic solvents as those used in the polymerization reaction of the above-mentioned (meth)acrylic copolymer (A) can be mentioned.

[0088] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, it may contain only one type of organic solvent, or may contain two or more types of organic solvent.

[0089] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be set appropriately within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.

[0090] [Other ingredients] The pressure-sensitive adhesive composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, provided that the effects of the composition are not impaired. Examples of other components include various additives such as polymers other than the (meth)acrylic copolymer (A), crosslinking catalysts, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.

[0091] When the pressure-sensitive adhesive composition of the present disclosure contains other components, the contents of the other components are not particularly limited and can be set appropriately within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.

[0092] <<Applications>> The pressure-sensitive adhesive composition of the present disclosure is resistant to whitening even when placed in a high-temperature, high-humidity environment, and can form a pressure-sensitive adhesive layer that exhibits high adhesive strength to an adherend and is resistant to yellowing even when placed in a high-temperature environment, making it suitable as a pressure-sensitive adhesive composition for use in touch panels. The adhesive composition of the present disclosure is preferably used, for example, for bonding a touch panel to a cover panel used for protecting the touch panel, and for bonding a liquid crystal display to a touch sensor.The adhesive composition of the present disclosure is also preferably used, for example, for bonding components of a touch sensor.Specifically, the adhesive composition of the present disclosure is suitable as an adhesive composition used when manufacturing a touch sensor by bonding various components of a touch sensor such as a glass substrate, a transparent conductive film, and a design film. The adhesive composition of the present disclosure is capable of forming an adhesive layer that exhibits high adhesive strength to an adherend and is resistant to yellowing, even when placed in an environment at a higher temperature than before (e.g., 130°C), and is therefore particularly suitable as an adhesive composition for use in in-vehicle touch panels, which have in recent years been required to have durability at higher temperatures, specifically as an adhesive composition for use in touch panels mounted on in-vehicle display devices.

[0093] [Adhesive sheet for touch panels] The pressure-sensitive adhesive sheet for a touch panel of the present disclosure (hereinafter also simply referred to as an "adhesive sheet") includes a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for a touch panel of the present disclosure described above. The adhesive layer of the adhesive sheet of the present disclosure is not easily whitened even when placed in a high-temperature and high-humidity environment. In addition, the adhesive layer of the adhesive sheet of the present disclosure exhibits high adhesive strength to an adherend and is not easily yellowed even when placed in a high-temperature environment. For this reason, the adhesive sheet of the present disclosure is suitable as an adhesive sheet used for a touch panel. The adhesive layer of the adhesive sheet of the present disclosure exhibits high adhesive strength to an adherend and is resistant to yellowing, even when placed in an environment at a higher temperature than before (for example, 130° C.). Therefore, the adhesive sheet of the present disclosure is particularly suitable as an adhesive sheet used in an in-vehicle touch panel, which has recently been required to have durability at higher temperatures, specifically, as an adhesive sheet used in a touch panel mounted on an in-vehicle display device.

[0094] The pressure-sensitive adhesive sheet of the present disclosure may be a substrate-free pressure-sensitive adhesive sheet that does not have a substrate, or a substrate-containing pressure-sensitive adhesive sheet that has a pressure-sensitive adhesive layer on one or both sides of a substrate. When the pressure-sensitive adhesive sheet of the present disclosure is a substrate-free type pressure-sensitive adhesive sheet having no substrate, or a substrate-containing type pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer on one side of a substrate, the exposed surface of the pressure-sensitive adhesive layer may be protected by a release film.

[0095] The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). An example of the resin film is a polyester film, typically a polyethylene terephthalate (PET) film. Examples of the release agent include silicone-based release agents (eg, silicone), wax-based release agents (eg, paraffin wax), and fluorine-based release agents (eg, fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive sheet of the present disclosure is put to practical use, and is peeled off when in use.

[0096] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is generally from 1 μm to 300 μm, preferably from 5 μm to 200 μm, and more preferably from 10 μm to 150 μm.

[0097] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by the following method. The arithmetic mean value of the thicknesses of the adhesive layer measured at 10 randomly selected points in the thickness direction of the adhesive layer is calculated, and the obtained value is regarded as the average thickness of the adhesive layer. The thickness of the adhesive layer is measured using a film thickness meter.

[0098] When the pressure-sensitive adhesive sheet of the present disclosure includes a substrate, the substrate is not particularly limited as long as a pressure-sensitive adhesive layer can be formed on the substrate. Examples of the substrate include films containing resins such as polyolefin resins (e.g., polyethylene (PE) and polypropylene (PP)), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetyl cellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.

[0099] The surface of the substrate on which the adhesive layer is provided may be subjected to a surface treatment such as corona discharge treatment or plasma discharge treatment (so-called adhesion enhancing treatment) in order to improve adhesion between the substrate and the adhesive layer.

[0100] The substrate may contain various additives, such as plasticizers, colorants (eg, dyes and pigments), heat stabilizers, light stabilizers, antistatic agents, flame retardants, antioxidants, and the like. The substrate may be partially or entirely patterned.

[0101] The thickness of the substrate is not particularly limited, but is generally 5 μm to 500 μm, preferably 10 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 10 μm to 100 μm.

[0102] "Substrate thickness" in this disclosure means the average thickness of the substrate. The average thickness of the substrate is a value measured by a method conforming to the above-mentioned method for measuring the average thickness of the pressure-sensitive adhesive layer.

[0103] [Method of manufacturing adhesive sheets for touch panels] The method for producing the adhesive sheet for a touch panel (i.e., the adhesive sheet) of the present disclosure is not particularly limited. The adhesive sheet of the present disclosure can be produced by a known method. The pressure-sensitive adhesive sheet of the present disclosure can be produced, for example, by the following method.

[0104] When the adhesive sheet of the present disclosure is a substrate-free adhesive sheet, first, the adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film.Then, the formed coating film is dried to form an adhesive film on the release film.Then, the exposed surface of the formed adhesive film is laminated and bonded to the easy-release treated surface of a separately prepared release film, and then cured to produce a substrate-free adhesive sheet having a laminated structure of release film / adhesive layer / release film.

[0105] When the adhesive sheet of the present disclosure is a substrate-type adhesive sheet, first, the adhesive composition of the present disclosure is applied to the easy-adhesion-treated surface of the substrate to form a coating film on the substrate. Then, the formed coating film is dried to form an adhesive film on the substrate. Then, the exposed surface of the formed adhesive film is laminated on the easy-release-treated surface of the release film, and then cured to produce a substrate-type adhesive sheet having a laminated structure of release film / adhesive layer / substrate.

[0106] When the pressure-sensitive adhesive sheet of the present disclosure is a substrate-containing pressure-sensitive adhesive sheet, another method may be mentioned, for example, the following method. The adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then laminated to the easy-adhesion treated surface of a substrate, and then cured to produce a substrate-type adhesive sheet having a laminated structure of substrate / adhesive layer / release film.

[0107] The method for applying the pressure-sensitive adhesive composition is not particularly limited. Examples of methods for applying the pressure-sensitive adhesive composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the adhesive composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the adhesive layer to be formed.

[0108] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 to 180 seconds.

[0109] The curing is carried out, for example, for 2 to 7 days in an environment with an atmospheric temperature of 20° C. to 35° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH). EXAMPLES

[0110] The pressure-sensitive adhesive composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.

[0111] [Production of (meth)acrylic copolymer] [Manufacturing example A-1] In a reaction vessel of a functionalization apparatus equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer, 400 parts by mass of ethyl acetate [organic solvent] was charged. Next, in another vessel, 300.0 parts by mass of a monomer mixture consisting of 180 parts by mass of ethyl acrylate [EA; acrylic acid alkyl ester monomer], 12 parts by mass of n-butyl acrylate [n-BA; acrylic acid alkyl ester monomer], and 108 parts by mass of 2-hydroxyethyl acrylate [2HEA; monomer having a hydroxyl group] was prepared. After this prepared monomer mixture was charged in the reaction vessel, it was heated to 70°C. Next, under the above temperature conditions, a solution X obtained by mixing 15 parts by mass of ethyl acetate and 0.012 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator] was successively dropped into the reaction vessel over 10 minutes. After the dropwise addition of solution X was completed, solution Y, which was a mixture of 30 parts by mass of ethyl acetate and 0.014 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator], was successively dropped into the reaction vessel over 85 minutes. After the dropwise addition of solution Y was completed, the mixture was held for 300 minutes to complete the polymerization reaction. Next, the solution obtained by the completion of the polymerization reaction was diluted with ethyl acetate to a solid content concentration of 40% by mass to obtain a solution of (meth)acrylic copolymer A-1.

[0112] The term "solid content" used herein means the mass ratio of the (meth)acrylic copolymer A-1 in the solution of the (meth)acrylic copolymer A-1. The same applies to each of the solutions of the (meth)acrylic copolymers A-2 to A-13 produced below.

[0113] [Production Examples A-2 to A-8 and A-11 to A-13] In Production Examples A-2 to A-8 and A-11 to A-13, the monomer composition of the (meth)acrylic copolymer was changed to the monomer composition shown in Table 1, and the polymerization temperature, polymerization time, amount of organic solvent used, amount of polymerization initiator used, etc. were appropriately adjusted, but the same operation as in Production Example A-1 was performed to obtain solutions of (meth)acrylic copolymers A-2 to A-8 and A-11 to A-13 each having a solid content concentration of 40 mass%.

[0114] [Production Examples A-9 and A-10] In Production Examples A-9 and A-10, the same operation as in Production Example A-1 was carried out except that the polymerization temperature, polymerization time, amount of organic solvent used, amount of polymerization initiator used, etc. were appropriately adjusted, and solutions of (meth)acrylic copolymers A-9 and A-10 each having a solid content concentration of 40 mass% were obtained.

[0115] Table 1 shows the monomer compositions (unit: mass%) of the (meth)acrylic copolymers A-1 to A-13, the glass transition temperatures (Tg) of the (meth)acrylic copolymers A-1 to A-13, and the weight average molecular weights (Mw) of the (meth)acrylic copolymers A-1 to A-13.

[0116] The glass transition temperatures of the (meth)acrylic copolymers A-1 to A-13 were calculated by the same method as the above-mentioned method for calculating the glass transition temperature of the (meth)acrylic copolymer (A). The weight average molecular weights of the (meth)acrylic copolymers A-1 to A-13 were measured by the same method as the above-mentioned method for measuring the weight average molecular weight of the (meth)acrylic copolymer (A).

[0117] Of the (meth)acrylic copolymers A-1 to A-13 obtained above, the (meth)acrylic copolymers A-1 to A-12 correspond to the (meth)acrylic copolymer (A) in the present disclosure.

[0118] [Table 1]

[0119] Details of each monomer listed in Table 1 are as follows. <(Meth)acrylic acid alkyl ester monomer> "EA": Ethyl acrylate "n-BA": n-butyl acrylate "2EHA": 2-Ethylhexyl acrylate "MA": Methyl acrylate <Monomers having hydroxyl groups> "2HEA": 2-hydroxyethyl acrylate "4HBA": 4-hydroxybutyl acrylate <Monomers having a carboxy group> "AA": acrylic acid

[0120] In Table 1, "-" in the monomer composition column means that the monomer in that column was not used.

[0121] [Preparation of Adhesive Composition] Example 1 100 parts by mass (solid content equivalent) of the solution of the (meth)acrylic copolymer A-1, 0.5 parts by mass (solid content equivalent) of ADK STAB (registered trademark) AO-80 (manufactured by ADEKA CORPORATION) which is a phenol-based antioxidant (B), 0.10 parts by mass (solid content equivalent) of ADK STAB (registered trademark) 3010 (manufactured by ADEKA CORPORATION) which is an antioxidant (C), and 0.2 parts by mass (solid content equivalent) of TAKENATE (registered trademark) D-110N (manufactured by Mitsui Chemicals, Inc.) which is an isocyanate-based crosslinking agent were thoroughly mixed to obtain a pressure-sensitive adhesive composition of Example 1.

[0122] [Examples 2 to 23] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 2, thereby obtaining each of the adhesive compositions of Examples 2 to 23.

[0123] [Comparative Examples 1 to 8] The same procedure as in Example 1 was carried out except that the formulation of the adhesive composition in Example 1 was changed to the formulation shown in Table 3, to obtain each of the adhesive compositions of Comparative Examples 1 to 8.

[0124] [Table 2]

[0125] [Table 3]

[0126] In Tables 2 and 3, "-" means that there is no corresponding item in that column. In Tables 2 and 3, the ratio of the mass content of the phenolic antioxidant (B) to the mass content of the antioxidant (C) other than a phenolic antioxidant in the pressure-sensitive adhesive composition is represented as "(B) / (C)".

[0127] Details of each component listed in Table 2 and / or Table 3 are as follows. [Phenol-based antioxidants] [Phenol-based antioxidant (B)] "ADEKA STAB AO-80" [Product name, molecular weight: 741, number of aromatic rings in one molecule: 2, polymerizable group: none, manufactured by ADEKA Corporation] "ADEKA STAB AO-30" [Product name, molecular weight: 545, number of aromatic rings in one molecule: 3, polymerizable group: none, manufactured by ADEKA Corporation] "ADEKA STAB AO-60" [Product name, molecular weight: 1178, number of aromatic rings in one molecule: 4, polymerizable group: none, manufactured by ADEKA Corporation] "Tocopherol" (trade name, molecular weight: 430, number of aromatic rings in one molecule: 1, polymerizable group: none, manufactured by Mitsubishi Chemical Foods Corporation) The above "ADK STAB" is a registered trademark.

[0128] [Phenol-based antioxidants other than phenol-based antioxidant (B)] "2,6-di-t-butyl-p-cresol" (trade name, molecular weight: 220, number of aromatic rings in one molecule: 1, polymerizable group: none, manufactured by Tokyo Chemical Industry Co., Ltd.) "Sumilizer GS" (product name, molecular weight: 548, number of aromatic rings in one molecule: 2, polymerizable group: yes, manufactured by Sumitomo Chemical Co., Ltd.) The above "Sumilizer" is a registered trademark.

[0129] [Antioxidants other than phenolic antioxidants (C)] "ADEKA STAB 3010" [Product name, phosphorus-based antioxidant (phosphite ester compound), molecular weight: 503, number of aromatic rings in one molecule: 0, polymerizable group: none, manufactured by ADEKA Corporation] "ADEKA STAB AO-26" [Product name, sulfur-based antioxidant (thioether compound), number of aromatic rings in one molecule: 2, polymerizable group: none, manufactured by ADEKA Corporation] The above "ADK STAB" is a registered trademark.

[0130] [Crosslinking Agent] <Isocyanate-based crosslinking agent> "Takenate D-110N" [product name, adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP), solid content concentration: 75% by mass, manufactured by Mitsui Chemicals, Inc.] The above "Takenate" is a registered trademark.

[0131] [Preparation of adhesive sheets for evaluation] 1. Evaluation Adhesive Sheet X The adhesive composition prepared above was applied to the easy-release treated surface of a release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been treated for easy peeling with a silicone-based release treatment agent to form a coating film. The amount of the adhesive composition applied was such that the thickness of the adhesive layer finally formed was 50 μm. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100° C. and a drying time of 2 minutes to form an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated on the easy-release treated surface of a release film [trade name: Film Byna (registered trademark) 25E-0010 BD, thickness: 25 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been treated for easy peeling with a separately prepared silicone-based release treatment agent, and then the film was left to stand for 4 days in an environment of an atmospheric temperature of 23° C. and 50% RH to be aged, and a non-substrate type adhesive sheet was produced. The prepared adhesive sheet was used as an adhesive sheet for evaluating adhesive strength, designated as evaluation adhesive sheet X. Evaluation adhesive sheet X had a laminated structure of release film / adhesive layer (thickness: 50 μm) / release film.

[0132] 2. Evaluation Adhesive Sheet Y The adhesive composition prepared above was applied to the easy-release treated surface of a release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been treated for easy peeling with a silicone-based release treatment agent to form a coating film. The amount of the adhesive composition applied was such that the thickness of the adhesive layer finally formed was 150 μm. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100° C. and a drying time of 2 minutes to form an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated on the easy-release treated surface of a release film [trade name: Film Byna (registered trademark) 25E-0010 BD, thickness: 25 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been treated for easy peeling with a separately prepared silicone-based release treatment agent, and then the film was left to stand for 4 days in an environment of an atmospheric temperature of 23° C. and 50% RH to be aged, and a non-substrate type adhesive sheet was produced. The prepared pressure-sensitive adhesive sheet was used as the pressure-sensitive adhesive sheet for evaluation of yellowing and whitening, designated as evaluation pressure-sensitive adhesive sheet Y. Evaluation pressure-sensitive adhesive sheet Y had a laminated structure of release film / pressure-sensitive adhesive layer (thickness: 150 μm) / release film.

[0133] [Measurement and Evaluation] 1. Adhesive strength The method of preparing the test piece and the method of measuring the adhesive strength in the adhesive strength evaluation test were in accordance with the method described in JIS Z 0237: 2009. The specific method is as follows.

[0134] (1) Early period One release film [product name: Film Byna (registered trademark) 25E-0010 BD] of the evaluation adhesive sheet X prepared above was peeled off, and the film was placed on the easy-adhesion treated surface of a PET film [product name: Cosmoshine (registered trademark) A4100, thickness: 100 μm, manufactured by Toyobo Co., Ltd.], and the film was pressed and bonded by passing through a pressure nip roll, and then cut into a size of 25 mm × 150 mm (long side) to prepare an evaluation adhesive sheet piece X1. Next, the release film [product name: Film Byna (registered trademark) 100E-0010 No. 23] of the prepared evaluation adhesive sheet piece X1 [composition: release film / adhesive layer / PET film] was peeled off, and the surface of the adhesive layer exposed by peeling was placed on one side of a glass plate [optical soda glass, thickness: 1.8 mm, size: 250 mm × 200 mm, manufactured by Matsunami Glass Industry Co., Ltd.] and bonded to prepare a laminate. The laminate prepared has a laminated structure of glass plate (adherend) / evaluation adhesive sheet piece X2 [structure: adhesive layer / PET film]. Next, the prepared laminate was left to stand for 24 hours in an environment with an atmospheric temperature of 23°C and 50% RH to prepare a test piece for evaluating the initial adhesive strength. For this test piece, the adhesive strength (unit: N / 25 mm) when the evaluation adhesive sheet piece X2 was peeled off from the glass plate at 180° in the long side (150 mm) direction was measured using a single column type material testing machine [model number: STA-1225] manufactured by A&D Co., Ltd. as a measuring device under the conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Then, evaluation was performed according to the following evaluation criteria. The results are shown in Table 4. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.

[0135] -Evaluation criteria- A: The adhesive strength was 25N / 25mm or more. B: The adhesive strength was 20N / 25mm or more and less than 25N / 25mm. C: The adhesive strength was 15 N / 25 mm or more and less than 20 N / 25 mm. D: The adhesive strength was less than 15 N / 25 mm.

[0136] (2) After heat resistance test One release film [product name: Film Byna (registered trademark) 25E-0010 BD] of the evaluation adhesive sheet X prepared above was peeled off, and the film was placed on the easy-adhesion treated surface of a PET film [product name: Cosmoshine (registered trademark) A4100, thickness: 100 μm, manufactured by Toyobo Co., Ltd.], and the film was pressed and bonded by passing through a pressure nip roll, and then cut into a size of 25 mm × 150 mm (long side) to prepare an evaluation adhesive sheet piece X1. Next, the release film [product name: Film Byna (registered trademark) 100E-0010 No. 23] of the prepared evaluation adhesive sheet piece X1 [composition: release film / adhesive layer / PET film] was peeled off, and the surface of the adhesive layer exposed by peeling was placed on one side of a glass plate [optical soda glass, thickness: 1.8 mm, size: 250 mm × 200 mm, manufactured by Matsunami Glass Industry Co., Ltd.] and bonded to prepare a laminate. The laminate prepared has a laminated structure of glass plate (adherend) / evaluation adhesive sheet piece X2 [structure: adhesive layer / PET film]. Next, the prepared laminate was left to stand in an environment with an atmospheric temperature of 130°C for 15 days to prepare a test piece for evaluating the adhesive strength after the heat resistance test. For this test piece, the adhesive strength (unit: N / 25mm) when the evaluation adhesive sheet piece X2 was peeled off from the glass plate at 180° in the long side (150mm) direction was measured using a single column type material testing machine [model number: STA-1225] manufactured by A&D Co., Ltd. as a measuring device under the conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300mm / min. Then, evaluation was performed according to the following evaluation criteria. The results are shown in Table 4. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.

[0137] -Evaluation criteria- A: The adhesive strength was 25N / 25mm or more. B: The adhesive strength was 20N / 25mm or more and less than 25N / 25mm. C: The adhesive strength was 15 N / 25 mm or more and less than 20 N / 25 mm. D: The adhesive strength was less than 15 N / 25 mm.

[0138] 2. Yellowing One release film [trade name: Film Byna (registered trademark) 25E-0010 BD] of the evaluation adhesive sheet X prepared above was peeled off, and it was placed on the easy-adhesion treated surface of a PET film [trade name: Cosmoshine (registered trademark) A4100, thickness: 100 μm, manufactured by Toyobo Co., Ltd.], and it was pressed and bonded by passing through a pressure nip roll, and then it was cut into a size of 50 mm × 70 mm (long side) to prepare an evaluation adhesive sheet piece Y1. Next, the release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23] of the prepared evaluation adhesive sheet piece Y1 [composition: release film / adhesive layer / PET film] was peeled off, and the surface of the adhesive layer exposed by peeling was placed on one side of a glass plate [optical soda glass, thickness: 1.8 mm, size: 250 mm × 200 mm, manufactured by Matsunami Glass Industry Co., Ltd.], and it was pressed and bonded by passing through a pressure nip roll to prepare a laminate. The laminate thus prepared had a laminate structure of glass plate (adherend) / evaluation adhesive sheet piece Y2 [structure: adhesive layer / PET film]. The laminate thus prepared was then left to stand for 15 days in an environment at an atmospheric temperature of 130° C. to prepare a test piece for evaluating yellowing after a heat resistance test. * The value was measured using a spectrophotometer (model: SE6000, manufactured by Nippon Denshoku Kogyo Co., Ltd.) and the b * From the value, b of PET film * The value obtained by subtracting the value from the evaluation value was used as the "evaluation value," and evaluation was performed according to the following evaluation criteria. The results are shown in Table 4. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.

[0139] -Evaluation criteria- A: The evaluation value was less than 0.5. B: The evaluation value was 0.5 or more and less than 0.8. C: The evaluation value was 0.8 or more and less than 1.0. D: The evaluation value was 1.0 or more.

[0140] 3.Whitening One release film [trade name: Film Byna (registered trademark) 25E-0010 BD] of the evaluation adhesive sheet X prepared above was peeled off, and it was placed on the easy-adhesion treated surface of a PET film [trade name: Cosmoshine (registered trademark) A4100, thickness: 100 μm, manufactured by Toyobo Co., Ltd.], and it was pressed and bonded by passing through a pressure nip roll, and then it was cut into a size of 50 mm × 70 mm (long side) to prepare an evaluation adhesive sheet piece Y1. Next, the release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23] of the prepared evaluation adhesive sheet piece Y1 [composition: release film / adhesive layer / PET film] was peeled off, and the surface of the adhesive layer exposed by peeling was placed on one side of a glass plate [optical soda glass, thickness: 1.8 mm, size: 250 mm × 200 mm, manufactured by Matsunami Glass Industry Co., Ltd.], and it was pressed and bonded by passing through a pressure nip roll to prepare a laminate. The laminate prepared has a laminated structure of glass plate (adherend) / evaluation adhesive sheet piece Y2 [structure: adhesive layer / PET film]. Next, the prepared laminate was left to stand for 7 days in an environment of 85°C and 95% RH, and used as a test piece for evaluating whitening after the moist heat resistance test. The haze values ​​(unit: %) of this test piece and the above glass plate were measured using a haze meter [model number: NDH 5000SP, manufactured by Nippon Denshoku Industries Co., Ltd.], and the value obtained by subtracting the haze value of the glass plate from the haze value of the test piece was taken as the "evaluation value (unit: %)", and evaluation was performed according to the following evaluation criteria. The results are shown in Table 4. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.

[0141] -Evaluation criteria- A: The evaluation value was less than 0.10%. B: The evaluation value was 0.10% or more and less than 0.50%. C: The evaluation value was 0.50% or more and less than 1.00%. D: The evaluation value was 1.00% or more.

[0142] [Table 4]

[0143] As shown in Table 4, it was confirmed that the adhesive layers formed using the adhesive compositions of Examples 1 to 23 were resistant to whitening even when placed in a high-temperature, high-humidity environment, and exhibited high adhesion to the adherend and were resistant to yellowing even when placed in a high-temperature environment.

[0144] On the other hand, the adhesive layer formed from the adhesive composition of Comparative Example 1, in which the content of structural units derived from monomers having hydroxyl groups in the (meth)acrylic copolymer was less than 18 mass% relative to the total structural units, showed significant whitening when placed in a high-temperature, high-humidity environment. The adhesive layer formed from the adhesive composition of Comparative Example 2, which did not contain either the phenolic antioxidant (B) or the antioxidant other than a phenolic antioxidant (C), showed a significant decrease in adhesive strength to the adherend when placed in a high-temperature environment. The adhesive layer formed from the adhesive composition of Comparative Example 3, in which the content of the phenolic antioxidant (B) was less than 0.1 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, showed a significant decrease in adhesive strength to the adherend when placed in a high-temperature environment. The adhesive layer formed from the adhesive composition of Comparative Example 4, in which the content of the phenolic antioxidant (B) exceeded 3.0 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, yellowed significantly when placed in a high-temperature environment. The adhesive layer formed from the adhesive composition of Comparative Example 5, in which the content of antioxidant (C) other than phenol-based antioxidants was less than 0.05 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, yellowed significantly when placed in a high-temperature environment. The adhesive layer formed from the adhesive composition of Comparative Example 6, in which the content of the antioxidant (C) other than the phenol-based antioxidant exceeded 0.50 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, had excessively low initial adhesive strength to the adherend, and the adhesive strength was further reduced by being placed in a high-temperature environment. The adhesive layer formed from the adhesive composition of Comparative Example 7, which contained a phenolic antioxidant not corresponding to the phenolic antioxidant (B) instead of the phenolic antioxidant (B), specifically a phenolic antioxidant having a molecular weight of less than 300 and having no polymerizable group, showed a significant decrease in adhesive strength to an adherend when placed in a high-temperature environment. The adhesive layer formed by the adhesive composition of Comparative Example 8, which contained a phenolic antioxidant not corresponding to the phenolic antioxidant (B) instead of the phenolic antioxidant (B), specifically, a phenolic antioxidant having a molecular weight of 300 or more and having a polymerizable group, exhibited a significant decrease in adhesive strength to an adherend when placed in a high-temperature environment. Moreover, the adhesive layer formed by the adhesive composition of Comparative Example 8 significantly yellowed when placed in a high-temperature environment.

Claims

1. a (meth)acrylic copolymer (A) containing 18% by mass or more and 50% by mass or less of structural units derived from a monomer having a hydroxyl group and 50% by mass or more and 82% by mass or less of structural units derived from a (meth)acrylic acid alkyl ester monomer, based on the total structural units, and having a weight average molecular weight of 100,000 to 1,000,000 and a glass transition temperature of -50°C to -5°C; (B) a phenol-based antioxidant having a molecular weight of 300 or more and no polymerizable group; and an antioxidant (C) other than a phenol-based antioxidant, the content of the phenol-based antioxidant (B) is 0.1 parts by mass to 3.0 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer (A); the content of the antioxidant (C) other than the phenol-based antioxidant is 0.05 parts by mass to 0.50 parts by mass based on 100 parts by mass of the (meth)acrylic copolymer (A); The pressure-sensitive adhesive composition for touch panels, wherein the phenol-based antioxidant (B) is a compound having 1 to 3 aromatic rings in one molecule.

2. 2. The pressure-sensitive adhesive composition for touch panels according to claim 1, wherein the antioxidant (C) other than the phenol-based antioxidant is at least one antioxidant selected from the group consisting of phosphorus-based antioxidants and sulfur-based antioxidants.

3. 3. The pressure-sensitive adhesive composition for touch panels according to claim 1, wherein a ratio of a content mass of the phenol-based antioxidant (B) to a content mass of the antioxidant (C) other than the phenol-based antioxidant is 1.3 to 15.

0.

4. The pressure-sensitive adhesive composition for touch panels according to any one of claims 1 to 3, wherein the (meth)acrylic copolymer (A) has a weight average molecular weight of 200,000 to 900,000.

5. The pressure-sensitive adhesive composition for touch panels according to any one of claims 1 to 4, wherein the (meth)acrylic copolymer (A) has a glass transition temperature of -40°C to -5°C.

6. The pressure-sensitive adhesive composition for a touch panel according to any one of claims 1 to 5, further comprising an isocyanate-based crosslinking agent.

7. The pressure-sensitive adhesive composition for a touch panel according to any one of claims 1 to 6, which is used for an in-vehicle touch panel.

8. An adhesive sheet for a touch panel, comprising an adhesive layer formed from the adhesive composition for a touch panel according to any one of claims 1 to 6.

9. The pressure-sensitive adhesive sheet for a touch panel according to claim 8 , which is used for an in-vehicle touch panel.

Citation Information

Patent Citations

  • Self-adhesive for tin-doped indium oxide film, and double-sided self-adhesive sheet

    JP2012092184A

  • Hot-melt adhesive

    JP2012177009A

  • Adhesive composition and adhesive tape

    JP2014088468A

  • Optical double-sided adhesive sheet

    JP2016094569A

  • Adhesive and adhesive sheet

    JP2020015782A